From a grand hotel to an urban symbol: the Astor Hotel in old and new Tianjin - Taoyu Yang (Built Heritage)
Abstract This article examines the enduring iconicity, multifaceted functions, and changing meanings of the Astor Hotel in Tianjin—one of the first international hotels in modern China—from the mid-19th century to the 21st century. Originally built more than 150 years ago, the Astor Hotel still stands exactly where it did in the former British Concession in Tianjin. This hotel was not only a venue boasting Tianjin’s most expensive accommodations but also a crucial site where politics, technology, economics, social, and cultural changes intersected and developed in its treaty port incarnation. Moreover, the expansion of the Astor Hotel evolved along with the development of Tianjin from a hypercolonial city to a Chinese-run metropolis. Shortly after the Communist Revolution in China, its ownership was overtaken by the Tianjin Municipal Government. Following a sequence of major renovations and commercial relaunches in the 1990s, the Astor Hotel was restored and reconstructed as an emblem of Tianjin’s historical status as an international and cosmopolitan city in China. Both continuity and changes will be emphasised in the discussion of the Astor Hotel’s history, as well as its multiple functions and shifting symbolic significance.